Government persuasion strategies for transport infrastructure adaptation: Spillover effects and social welfare impacts - Zheng, Shiyuan; Jiang, Changmin (Transportation research. Part B: methodological, 2025)
•We analyze the government’s strategies to persuade multiple transport facility operators to engage in adaptation projects.•A Bayesian persuasion model is developed to emphasize the spillover effects among operators’ projects and their externalities on social welfare.•When operators act independently, larger spillover effects result in either lower or higher social welfare, contingent on whether the adaptation projects have positive or negative impacts, respectively.•Operators facing the highest adaptation costs are more likely to be excluded from the government’s persuasion efforts. This paper explores the government's strategies to persuade multiple transport facility operators to undertake adaptation projects, particularly within the Asian doctrine governance regime, where the government exerts significant influence over facility operations. We develop a Bayesian persuasion model to analyze these strategies, focusing on the spillover effects among operators' projects and their externalities (both positive and negative) on social welfare. Our findings suggest that a straightforward signaling strategy, which directly advises operators on whether to invest, can effectively convey disaster information. When there are no spillover effects and the adaptation projects positively impact social welfare, the government should fully disclose disaster information and persuade operators based on their willingness to invest. However, higher adaptation costs or larger spillover effects complicate the government's persuasion efforts. To demonstrate the practical value of our theoretical framework, we apply our Bayesian persuasion model to the case of port adaptation in the Greater Bay Area in China. The model calibration results indicate that when operators act independently, larger spillover effects can lead to either lower or higher social welfare, depending on whether the adaptation projects have positive or negative impacts, respectively. When adaptation projects positively affect social welfare, operators' alliance strategies of joint adaptation investment or resource sharing enhance social welfare. If spillover effects exist among operators, a benefit distribution scheme based on the Shapley value can maintain stability within the grand coalition of all operators. Finally, increasing adaptation costs have uneven impacts on different operators, with those facing the highest costs being more likely to be excluded from the government's persuasion efforts.